Soil pollution indices under the effect of sludge - Shomar, Basem; Kalavrouziotis, Ioannis K.; Koukoulakis, Prodromos H.; Yahya, Alfred (Water, air & soil pollution, 2013)
A pot experiment was conducted in order to study the relationships of soil pollution indices to maize (Zea mays L.) growth characteristics and soil and plant heavy metal content, as well as the metal plant uptake. A completely randomized block design was used, including 11 treatments in three replications. The treatments applied were control (freshwater), four levels of inorganic NPK fertilizer combined with treated municipal wastewater and freshwater and three sludge levels (5, 25 and 50 %, respectively) in the presence of treated wastewater and freshwater, respectively. The mean effect of the applied sludge levels independent of the presence of the freshwater or wastewater contributed to the accumulation of heavy metals Cr, Cu, Zn and Mn in soil and in leaves. The soil pollution indices, i.e., pollution load index (PLI), elemental pollution index (EPI), total concentration factor and heavy metal load, showed that the soil had been polluted with heavy metals to a great extent. The application of sludge treatment affected positively the maize plant height, leaf number and the indices PLI and EPI. All pollution indices studied were positively related to plant leaf number and plant height, as well to heavy metal soil content.
Published online: 16 January 2013
Gesehen am 26.01.2022